1989
DOI: 10.1093/jnci/81.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Combination Bleomycin, Ifosfamide, and Cisplatin Chemotherapy in Cervical Cancer

Abstract: We report a phase II study of bleomycin, ifosfamide, and cisplatin (BIP) in cervical cancer. Our aims were to assess response rate, toxicity, and survival in women treated with this combination. Among 49 patients, 34 objective responses (69%) were seen, with 10 complete responses (20%). Toxic effects were assessed in 186 treatment cycles. All patients had alopecia and nausea and vomiting. Other effects included myelosuppression, infection, reduction in renal function, and disturbance of consciousness. These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Several combination chemotherapy regimens that contain cisplatin have been tested in phase II studies, and objective responses have been documented in 30 -70% of the patients, while the median overall survival time ranged between 7 and 12 months (Buxton et al, 1989;Murad et al, 1994;Long et al, 1995;Papadimitriou et al, 1997Papadimitriou et al, , 1999Rose et al, 1999). Although it is difficult to directly compare the relative merits of the combined regimens with the single agents, combination chemotherapy seems to be superior to single-agent therapy based on these phase II studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several combination chemotherapy regimens that contain cisplatin have been tested in phase II studies, and objective responses have been documented in 30 -70% of the patients, while the median overall survival time ranged between 7 and 12 months (Buxton et al, 1989;Murad et al, 1994;Long et al, 1995;Papadimitriou et al, 1997Papadimitriou et al, , 1999Rose et al, 1999). Although it is difficult to directly compare the relative merits of the combined regimens with the single agents, combination chemotherapy seems to be superior to single-agent therapy based on these phase II studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many combination chemotherapy regimens have also been explored during the last two decades. High response rates have been obtained in some studies, but it is difficult to assess the relative merits of the various regimens because of differences in patient selection (Buxton et al, 1989;Papadimitriou et al, 1999).…”
mentioning
confidence: 99%
“…Other non-GOG phase II trials in cervical cancer that are of considerable interest include that of Buxton et al [45], in which a combination of bleomycin, ifosfamide, and cisplatin yielded 34 objective responses (69%), including 10 complete responses, in a study group of 49 subjects. The regimen containing methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) has been the subject of two reports examining its role in advanced/recurrent cervical carcinoma: an overall response rate of 66% (including 21% complete responses) was observed in the study by Long et al [46], whereas objective responses were observed in 52% (including 11% complete responses) of subjects reported by Papadimitriou et al [47].…”
Section: The 76 Series and Other Phase II Studiesmentioning
confidence: 99%
“…The papers by Fiorica et al [44], Buxton et al [45], and Long et al [46], together with the GOG-76 trials [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], laid the foundation for the phase III GOG experience in metastatic cervical carcinoma.…”
Section: The 76 Series and Other Phase II Studiesmentioning
confidence: 99%
See 1 more Smart Citation